(untitled) - Hoffmann, Laurence D. (Boston, 2007)
The book introduces the application of calculus in real-world contexts. It provides the basic concepts of calculus that can be applied in business, economics, finance and investment; the life, health and invironmental science; the physical science; and the social sciences
Keywords: Calculus,Phép tính vi tích phân